فقہی احکام ِخمسہ کی اہمیت وعملی افادیت؛ایک تجزیاتی مطالعہ: An Analytical Study of the Practical Expediency & Importance of Five Jurisprudential Rules - Ahmad, Fazail Asrar; Ijaz, Prof. Dr. Muhammad (Al-Amīr Research Journal for Islamic Studies, 2023)
This article discusses importance and practical expediency of Five Well-known and most important traditional Sharia Rules i.e. Obligation, Desirable, Forbidden, Unpleasant and Acceptable. Since the early development of Islamic Jurisprudence, difference of opinion exists among the Founders, Jurists, Lawyers and Followers of Islam regarding determination of legal status of various religious commands. This is the reason that Islamic Jurists classified acts and omissions into five famous rules on the basis of their legal implications and far-reaching effects. The well-known types of Sharia rules and their further division are based on the extent of available freedom in their practice. These Sharia rules have been analyzed in the light of research writings of some of the famous and authentic Muslim jurists. This research shows the Practical benefits and implications of the five sharia rules. Special focus has been given to the connotation and interpretation of the concept of obligation and its related terms. Key Words: Sharia Rules, Commands, Islamic Law, Objectives, Limitations.